Numerical study on the factors affecting natural ventilation cooling and structural optimization of glass curing body temporary storage - Yuan Gao; Sihan Liu; Tianci Han; Kai Ma (International Journal of Advanced Nuclear Reactor Design and Technology)
Glass curing technology is a mature and effective technical means to deal with high level liquid waste produced by spent fuel reprocessing. The dry storage technology of glass curing body is a developing trend. In the natural ventilation cooling of glass curing body temporary storage, the structural design is crucial, which directly affects the safety and stability of the temporary storage. This paper investigates the effects of various structural parameters and the application of insulating materials on the natural ventilation cooling effectiveness of the temporary storage based on Computational Fluid Dynamics (CFD). The goal is to enhance natural ventilation and reduce the thermal impact of the glass curing body on the concrete structure of the temporary storage. The results show that the height of exhaust shaft, the number of exhaust shaft, the shape of exhaust shaft, annular gap between shaft and glass products, inclination angle of baffle inside intake shaft, the dimensions of intake shaft and ventilation mode are the key factors affecting the ventilation cooling of temporary storage. The cross-sectional area of the air inlet and outlet, and the transverse pitch of glass products have little impact on the ventilation and heat exchange in the temporary storage. The optimal structural arrangement is obtained. The natural ventilation cooling effect is optimal when insulating materials are installed on the top and all four side walls of the temporary storage. The research provides a theoretical basis for the structural design and optimization of glass curing body temporary storage.